0 - Editorial - Fuh, Divine (CODESRIA Bulletin, 2021)
This issue of the CODESRIA Bulletin is produced at the end of the 2013–2016 programme cycle, and therefore at the beginning of a new programatic cycle and strategic plan. The 2017–2021 programme cycle has been entrusted with: “Reaching New Frontiers in Social Science Research and Knowledge Production for African Transformation and Development.” The new strategic plan builds on the recommendations of major comprehensive internal reviews aimed at sharpening the council’s mandate to develop the social sciences and humanities in Africa for better transformation and development within the context of continual global changes. These include: review of the intellectual agenda, membership, governance and management. The new strategic plan builds on the achievements of the past strategic cycle, ensuring consolidation and renewal, and ushering innovations in programme delivery and management; deeply emphasising the importance of basic research, and its relevance for policy, as well as community and civil society engagements. The new strategic plan prioritises three key thematic areas: democratic processes, governance, citizenship and security; ecologies, economies and societies; and higher education dynamics in a changing Africa. In addition to these three thematic priorities, a set of six crosscutting themes meant to suffuse all CODESRIA research; training and publications have been set. These include: gender; generations; alternatives and futures; inequality, rurality and urbanity; and memory and history. Most notable is a re-imagination and narrowing of research vehicles such as the traditional National Working Groups, Comparative Research Networks, and Multinational Working Groups which have now been collapsed under one vehicle – the Meaning-Making Research Initiative (MRI) to offer researchers the space to carryout and produce deeper empirical but also much more theoretically grounded and policy relevant basic research. For this issue of the bulletin we put together some of the discussions on emergence held during the CODESRIA day and around which we invited a cross section of diverse researchers to offer reflections on how to build research futures or ‘futuristic’ research agendas for Africa with respect to its place in the world, and how to incorporate the world within the continent. They were asked to address what they consider to be the big issues, key questions and grand debates for the continent, and also what they identified as the next big issues and questions that we need to learn to deal with in order to emerge from our ‘development’ process. It is thus for this reason that some of the articles reflect on the place and role of research in Africa’s ‘emergence’. We set off with poetry, in an attempt to expand our pedagogies of knowledge within a context characterised by intergenerational ruptures around the focus and tools of knowledge production, leading to calls to interrogate, and in some cases, abandon the knowledge production enterprise. This is also to re-iterate CODESRIA’s long work in and commitment for interdisciplinary/transdisciplinary work with the social sciences and humanities. A change of practice in this particular issue is our experimentation with a methodology to approach the Pan- African experience that underpins CODESRIA as a space for conversations across all regions, genders, generations, disciplines and languages. Since it’s founding, CODESRIA adopted and continues to operate in four official languages: English, French, Portuguese and Arabic, with plans to expand to other African languages. For its forty-five years of existence and since the start of the Publications and Dissemination Programme, CODESRIA publications have provided a space for Pan-African discussions, enabled through simultaneous translation of key publications such as the bulletin. For years the secretariat has struggled with simultaneous publication of the bulletin in the four languages. In the end, the English edition was always printed first, followed thereafter by the French edition, and sometimes by the Portuguese, while there were always regular translations into Arabic. The consequences of these are diverse. Apart from ensuring that at every given moment every member of the community is informed about and participates in particular debates and conversations going on in the council, delayed translations also created delayed participation in debates, given that by the time these were translated into one language, the others would have moved on, meaning that speakers of one language were always in a situation of catching up. It is for this reason that in this special issue, we elected to publish the articles in their original languages, hoping to reactivate critical reflections on how to operationalise Pan-Africanism within a context of multilingualism. We believe this conversation is now absolutely necessary given the resurgence of the decolonisation and decoloniality debates. The debate over higher education reform and its relationship to knowledge production is one which preceeds the current generation of students and scholars, but has resurfaced as a core part of the reenergised struggles against decolonisation. Over the past five years, particularly Black students in South Africa, Ghana, the UK, the US and Brazil have taken issue at the symbols and resilience of colonial structures and institutions, especially in universities which have become the frontiers of this revolution. Charecterised by the topling and dismantling of colonial symbols such as protests against Cecil John Rhodes’ statue at the University of Cape Town and the ensuing anti-imperialist movements which emerged from these protests in Oxford and other universities across the world; there’s a renewed momentum to re-interrogate pedagogies of learning, knowledge production processes and practices and the ways in which they are grounded in local everyday experiences. A critique that has resurfaced is that even after more than fifty years of independence, universities serve as incubators for new strains of the modernising colonial project. Amongst these debates, the meaning, purpose and form of research, especially in the social sciences and humanities particularly with respect to the ethics of being, patriarchy, epistemic violence, hierarchies of research relationships, and appropriateness of tools are at the core of the renewed challenge to scientific authority and the relevance of research. As part of these critiques, calls for the university to be humane and questions about whether the university can be human and if it has the capacity to take the human seriously have exposed major loopholes in the universities and intergeneration' cleavages about how to reform. Key questions remain what the postcolonial university should do, what it should look like, how should it contribute to the transformation of society, and what should be the role of research institutions such as CODESRIA? We are told that Africa is rising. That the continent is at the verge of breaking its curse and reputation as the world’s “heart of darkness”. It is the time of ‘emergence’. ‘Emergence’ has dominated discussions and processes of political economy, development, growth and the post-structural adjustment era in Africa. These debates are centred around issues related to how we understand the place from which we emerge, the destination the process of emergence is supposed to take us to, and the process through which emergence is achieved. It is a notion that has come to dominate the political and economic lives of a number of countries on the continent seen to be the frontiers of growth, investment and therefore development. This is best illustrated in the now cliché examples of the covers of The Economist magazine between 2000 in which the continent was portrayed as a “The Hopeless Continent”, through to 2011 in which the continent was depicted as “Africa Rising”, and then 2013 in which the continent was represented as “Aspiring Africa”. Reports talk of economies sprouting opportunities, engendered by a growing educated and entrepreneurial class, which is supposedly reducing the poverty rates by creating new busines opportunities. This group is said to constitute part of the growing middle class that is redefining the African continent as a place of hope and investment – a place of the future, or futuristic if you prefer to be cool: a place of emergence. Yet, the resilience of poverty, the stubbornness of diseases such as malaria, the slow pace of progressive reforms on gender and sexuality, a rise in fundamentalist violence, an upsurge in African migrant deaths in the Mediterranean Sea, and civil struggles against tenacious dictatorial regimes are grim reminders of the divergence, contradictions, and, some argue, near false assumptions about an emerging Africa unsubstantiated by empirical research. The austerity programmes which were rolled out to recompose struggling post-independence states continue to entrench many african countries into deeper cycles of chronic credit with no signs of solvency or financial stability. The inequality margin has expanded even further. An Oxfam report released in January 2017 demonstrates that by the end of 2016, eight of the world’s richest men owned the same wealth value as 3.6 billion people, that is half of the world, with plans for even greater accumulation. How should research enter these conversations? How should scholars of African tackle a concept that like development starts off by infantilising and contraining the continent within a matrix in which they are coceived of as being entrapped in a never ending permanent dream of coming of age – that is, emerging? How do we as African researchers and research organisations locate ourselves within these debates? We must recognise and acknowledge the critical context in which we find ourselves – the human is under threat. We are facing extinction. And this is not just about the ecological challenges that are driving the sustainability and Anthropocene movement, but also particularly about the core values that frame and underpin human society and relations such as interdependency and mutual respect. Modernity and its accompanying projects such as development and democracy are no longer as tenable as promised and have not successfully created wealth, stability, harmony and equality. The last several years has seen an increase in right wing political and religious fundamentalism, leading to an increase in overt bigotry and hate-motivated violence worldwide. Our era is characterised by the resilience and further entrenchment of dictatorship, as well as the liberation and democratisation of tyranny. Evidence of this can be seen in the constitutional changes that certain governments are undertaking to eliminate presidential term limits, power hoarding in particular families and elite groups, and the normalisation of precarity as seen in the ‘international communities’’ neglect of certain sufferings and struggles. This has led to the delegitimisation and de facto irrelevance of rights instruments, pertaining to an increase in declarations of states of exceptions, especially in places where people imagine themselves as free of routine precarity. For these people, precarity is now inescapable pertaining to political radicalisation, financial instability, surging unemployment, disease outbreaks, and ecological collapse. To compound this, science is facing obfuscation in a phenomenon that is described by many as ‘the end of truth’, also made possible by the diminution of the academy and the loss of the university as repository of knowledge. In an era of temporality where one hundred and forty characters of a tweet attracts more attention and influences policy more that hundreds of pages of scientific evidence produced through years of laborious research, basic research is under threat, as also demonstrated in the increasing demand amongst funders for direct policy impacting research. What are the implications for knowledge production, especially for the continent? How should we as an organisation respond to these challenges? How do we remain relevant without seeming maladjusted? How do we uphold our mandate and protect our brand? Is it necessary to and how do we define a longer-term goal for CODESRIA’s activities? How do we ensure continuity while renewing? Do we need to and how should we clearly differentiate our future from the past? Do we need to rebrand and how should it happen? What are we, who should we serve and what have we become? What should our product be, how should it be packaged, what is our currency, and what are our terms of engagement? Fortunately, as Ebrima Sall indicated in an interview with Africa Business in January 2017 discussing the reasons for CODESRIA’s ranking as Africa’s top think tank, the council regularly undertakes wide-ranging processes of self-introspection and reform to leverage, improve and cement its position as the leading social science research organization in Africa, as well as a leading contributor to the broad visions for national, continental and global transformations currently undertaken in the continent. CODESRIA’s regular five-year programme cycle provides the opportunity for continues consolidation and renewal through collective reflection. Divine Fuh Head of Publications and Dissemination CODESRIA